Using Children’s Literature in the process of training retelling of preschool children (Pedagogy of Higher and Secondary Education, 2013)
Gordiy N. M.  Using Children’s Literature in the process of training retelling of preschool children.The article deals with the development of connected speech preschoolers, substantiates reasonable value of the use of literature for children with learning render, described performance levels of connected speech .
Keywords: connected speech; literature for children transferring; linguistic competence